Water – Handbook of the Anthropocene in Latin America IV - Susana Herrera-Lima; Ricardo A. Gutiérrez; Lourdes Sofía Mendoza Bohne (BiUP, 2025)
Conflicts and struggles like urbanization processes and the productive use of water have impacted the relationship of Latin American and Caribbean societies with water for centuries. This volume of the Handbook »The Anthropocene as Multiple Crisis« focuses on water in the main macro-regions of Latin America from the colonial regime to the contemporary era of the Anthropocene. The contributions enrich contemporary debates surrounding the genealogy of the Anthropocene in Latin America with critical perspectives from the social sciences and the humanities.